CULTURAL VALUES REFLECTED IN TV COMMERCIALS BY UNILEVER VIETNAM AND UNILEVER AMERICA = Những giá trị văn hóa được phản ánh qua quảng cáo của Unilever Việt Nam và Unilever Mỹ - Hoàng, Thị Thu Hiền (2020)
Unilever is the object of many studies. However, they just have been focus on economics field and business. My research focuses on cultural adaptation of Unilever in advertising in Vietnam and America markets. The aim of the study is finding out typical cultural values reflected in TV commercials by Unilever Vietnam and Unilever American. The data used for this study are taken from ten TV commercials which were broadcasted in the two studies countries. Qualitative content analysis is used for observation data. The process of data analysis goes through 3 stages: selection of video categories, each advertisement is carefully observed. Evidences for each video are analyzed to find out cultural values reflected. The analysis shows that typical cultural values of each country are clearly reflected in TV commercials by Unilever. Individualism, competitive trait and future orientation are reflected in most TV commercials by Unilever America.TV commercials by Unilever Vietnam express typical cultural values of Vietnamese such as collectivism, tradition orientation and family orientation. And another finding about the similarity is the collectivistic trait that is shown in advertisements by both Unilever Vietnam and Unilever America. From those, the research can come to the significant conclusion in the cultural adaptation strategy by Unilever in marketing.